AI and Nanotechnology for Healthcare: A survey - Rawat, Bhupesh; Bist, Ankur Singh; Supriyanti, Dedeh; Elmanda, Vonda; Sari, Siti Nurindah (APTISI Transactions on Management (ATM), 2023)
AI is today's wave of technology, and it caters to various problems. One of them is Nanotechnology. Nanotechnology is another thread of technology. The use of nanotechnology is well known, including in the health sector, cosmetic industry, and agriculture. The role of AI in healthcare is broad, from detecting lung disease to skin analysis. This study aims to explore healthcare possibilities by integrating AI and nanotechnology. The method of applying nanotechnology in the health sector uses a Nanomedicine Microscope. Nanomedicine is the medical application of nanotechnology used to diagnose, monitor, and control biological systems. Therefore, the author uses the Nanomedicine Microscope as the object in this study because the wonders of nanotechnology in various operations are also well established. The novelty in this paper focuses on AI and Nanotechnology together as possibilities for healthcare. AI and nanotechnology are two critical technologies. The ultimate goal is to integrate the uses and possibilities of these two technologies and do wonders in the healthcare domain. This study will benefit those working in AI and medicine. Nanotechnology integrating AI technology into the medical industry enables many conveniences, including task automation and analyzing large amounts of patient data for better, faster, and more affordable healthcare.